Simulation of Irrigation Uniformity and Optimization of Irrigation Technical Parameters Based on the SIRMOD Model under Alternate Furrow Irrigation†. (15th February 2017) - Wu, Di; Xue, Jingyuan; Bo, Xiaodong; Meng, Weichao; Wu, Youjie; Du, Taisheng
Abstract: To evaluate the irrigation distribution uniformity and optimize the suitable combination of irrigation technical parameters for alternate furrow irrigation (AFI) and conventional furrow irrigation (CFI), field experiments on maize were conducted during 2010 and 2012 at the Shiyanghe Experimental Station in the arid area of north‐west China. A surface irrigation simulation model (SIRMOD) was used to optimize the combination of irrigation technical parameters such as field slope, furrow length and inflow rate. From the distribution uniformity (DU) results calculated from measured data in field experiments, under the same kind of soil texture, using the AFI method in the field could improve irrigation distribution uniformity for 9.67, 3.16 and 3.44% under a slope 1.5, 2.0 and 3.0‰ respectively; the relative error of DU between the simulation value from SIRMOD and the calculated value from field experiment was 4.25%, which was in an acceptable range. On the other hand, combinations of irrigation technical parameters of the CFI and AFI methods were simulated using SIRMOD with the distribution uniformity being the evaluation index. For the irrigation technical parameters, field slope ranging from 0 to 3.0‰, inflow rate from 1.0 to 8.0 l s −1 and furrow length from 25 to 300 m were chosen in this paper. Copyright © 2017 John Wiley & Sons, Ltd.